INCLUSIVE LEARNING MODEL IN SPORTS MATRICULATION: ADAPTATION STRATEGY TO IMPROVE ACTIVE INVOLVEMENT OF 3T STUDENTS IN HIGHER EDUCATION - Damayanti, Yosephine Debbie; Wulanningtyas, Melania Eva (Universitas Negeri Semarang, 2025)
This study analyzes the effectiveness of an inclusive learning model in sports matriculation to increase the active involvement of 3T students in college. This model is implemented through an experience-based approach, social interaction, and adaptation strategies designed. The research method uses a qualitative approach with data collection techniques in the form of interviews, observations, documentation, and questionnaires to measure the level of student involvement. The results of the study indicate that the inclusive learning model increases student participation in discussions, group work, and practice-based activities. Students experience increased social skills, especially in communication and teamwork. Student self-confidence also increases along with the implementation of learning strategies that encourage their active involvement. In terms of understanding the material, practice-based and experimental methods are proven to be more effective than conventional lectures. This study provides insight into the importance of an inclusive approach in sports matriculation to increase the involvement of 3T students in college.